Digital Literacy on Project-Based Learning: Teacher and Student Perceptions - Fitrotul Mufaridah (Universitas Sulawesi Barat, 2025)
Project-based learning integrated with technology requires and hones many digital competencies of teachers and students. Digital literacy, as a step to strengthen the digital competencies of teachers and students, is a manifestation of the use of information and communication technology brought into 21st-century learning. This study aims to describe teachers' and students' perceptions of the effectiveness of digital literacy in project-based learning and how digital competencies are applied by both teachers and students in project-based learning. The results of this study show that digital literacy was implemented by teachers offering choices of relevant digital media for students to use in their projects, demonstrating examples of their usage and outcomes, and students then studying and selecting the most appropriate media for their projects. This method of implementing project-based learning encouraged the process of digital literacy among teachers and students. The study also found that students perceived the application of digital literacy as highly effective, particularly in terms of speed and ease of project completion. The multimodal approach encouraged them to become more independent, and this independence fostered their active engagement in completing their projects. Teachers observed that allowing students the freedom to choose digital modes for their projects promoted creativity in producing project outcomes. This study demonstrates that good implementation of digital literacy, with attention to creating interactive spaces, enables students to have positive experiences by granting them the freedom to select their digital modes within project-based learning. It recommends that future research develop models of digital literacy for project-based learning.